70 Gene expression at the 9p21 locus and cad risk. (9th June 2011) - Nelson, C P; Lundmark, P; Codd, V; Goodall, A H; Syvänen, A C; Samani, N J
Abstract : Background: Human chromosome 9p21 harbours a locus that affects risk of coronary artery disease (CAD) through an unknown mechanism. The variants at the locus most strongly associated with CAD lie in non-coding regions suggesting that the affect on CAD risk may be mediated through regulation of gene expression. We investigated the association of single nucleotide polymorphisms (SNPs) across the locus with expression of genes in the locus and compared this with association of the same SNPs with CAD risk. Methods: We quantified transcript levels for CDKN2A, CDKN2B, ARF and MTAP in circulating monocytes from 422 healthy blood donors and 386 CAD cases and obtained genotypes for SNPs in the 9p21 region in the same subjects using genome-wide platforms. We also quantified allelic expression (AE) for these genes and for ANRIL in 186 of the healthy blood donors. We compared expression quantitative trait loci (eQTL) associations for the genes with association findings for the same SNPs for CAD in the Wellcome Trust Case Control Consortium study. Results: In the global gene expression analysis, we found strong cis eQTLs for both CDKN2B (p=1.3×10 −38 ) and MTAP (p=6.6×10 −23 ), explaining 17.0% and 8.0% of the expression of these genes. AE analysis confirmed these findings (CDKN2B, p=6.0×10 −64 ; MTAP, p=1.4×10 −38 ) and also showed a significant cis-eQTL effect on ANRIL expression (p=3.5×10 −28 ). Interestingly, the SNPs associated with CDKN2B and ANRIL expression were the same. However, the SNPs showing e-QTL effects were distinct from SNPs that showed an association with CAD risk (p=2.2×10 −12 ). Even in the region with a physical overlap of variants affecting expression of CDKN2B/ANRIL and CAD risk, the effects of the respective variants were independent of each other. Expression of CDKN2A and ARF was low but did not show any obvious eQTL effect, or differences according to genotype at CAD-associated SNPs. Conclusions: Our findings in monocytes do not support the hypothesis that the chromosome 9p21 locus mediates CAD risk by affecting expression of the genes at the locus. The mechanism by which the chromosome 9p21 locus affects CAD risk requires further elucidation.